Manajemen Reproduksi Sapi Potong Untuk Peningkatan Produktivitas Peternakan Rakyat - Vivi (Jurnal Ilmu Peternakan Indonesia, 2025)
This study aims to analyze the reproductive management of beef cattle in smallholder farming systems and to identify the factors that influence their productivity. The research applied both descriptive-qualitative and quantitative methods, with data collected through interviews, field observations, and reproductive record analysis. The findings indicate that artificial insemination (AI) is the primary method applied by farmers, with an adoption rate of 85%. However, reproductive indicators such as service per conception (S/C), conception rate (CR), and calving interval (CI) remain below the ideal standards. The average S/C recorded was 1.9, the CR reached only 62%, and the CI ranged between 16–18 months. Nutritional deficiencies and reproductive health issues were identified as the main constraints, alongside limited farmer knowledge in estrus detection. Advanced reproductive technologies such as estrus synchronization and embryo transfer are still rarely implemented due to cost limitations, insufficient facilities, and lack of technical support. These findings highlight that improving beef cattle productivity through reproductive management requires an integrated approach, including improved feeding, reproductive health management, farmer training, and the adoption of appropriate reproductive technologies. With the right strategy, smallholder farming systems can significantly contribute to achieving national beef self-sufficiency.